PREVALENCE OF ANAEMIA AND FACTORS INFLUENCING ANAEMIA IN ADOLSCENT GIRLS IN URBAN AND RURAL AREA OF A SOUTH INDIAN CITY:A COMPARITIVE STUDY. - DR.G.SUDHA RANI; DR.M.L.SURYAPRABHA (International Journal of Pharma and Bio Sciences, 2013)
Adolescents in India represent over 1/5th (22.3%) of the total population. Iron deficiency anaemia is the commonest medical disorder and is a problem of serious public health condition with epidemic proportions. It has an impact on all developments. To determine prevalence of anaemia among adolescent girls and to study the various factors associated with anaemia in urban and rural field practice areas of Osmania Medical College. A total of 760 adolescent girls (380 in each area) were interviewed and examined. BMI was calculated with anthropometric calculator available in WHO Anthroplus. Method of haemoglobin estimation is by cyneametheheamoglobin. Anaemia was classified based on WHO classification. The prevalence of anaemia was 74.5% and 82.6% in rural and urban area respectively. Severe anaemia was more in urban area when compared to rural area i.e. 8.4% & 3.4% respectively. Prevalence of Anaemia found to be increased with age. In rural area, 84 (87.5%) of girls were anaemic who were menstruating more than 7 days and only 31(45.6%) were anaemic who were menstruating less than 3 days. In urban area, 91(79.8%) of girls are anaemic who were menstruating more than 7 days and only 14(31.1%) were anaemic who were menstruating less than 3 days. Majority of married subjects were anaemic in both urban (82.4%) and rural (95.8%) area. Religion did not have a significant relation with anaemia.